Development of 68Ga‐labeled fatty acids for their potential use in cardiac metabolic imaging. (15th June 2014) - Jindal, Akanksha; Mathur, Anupam; Pandey, Usha; Sarma, H. D.; Chaudhari, Pradip; Dash, Ashutosh
<x xml:space="preserve">Abstract</x> While [11C]palmitate continues to be a promising tracer for cardiovascular Positron Emission Tomography (PET) imaging, unfavourable logistics due to the short half‐life of 11C (20 min) and cumbersome labeling methodologies are the major impediments that limit its widespread use. In order to circumvent such limitations, an attempt has been made to explore the potential of 68Ga‐labeled fatty acid analogs for metabolic imaging owing to the availability of 68Ga through a 68Ge/68Ga generator on an on‐demand basis. In this study, two fatty acid conjugates were synthesized by conjugation of p‐SCN‐benzyl NOTA with the ω‐amino group of 11‐amino undecanoic acid and 12‐amino dodecanoic acid, respectively, under alkaline conditions. Both derivatives were radiolabeled in high yields with 68Ga obtained from an in‐house 68Ge/68Ga generator. Biodistribution studies in Swiss mice showed reasonable myocardial uptake at 2 min for both derivatives (7.4 ± 2.8% ID/g for 11‐carbon fatty acid‐NOTA conjugate and 6.4 ± 2.1% ID/g for 12‐carbon fatty acid‐NOTA conjugate), which cleared rapidly over 30 min. However, significant activity was found in blood for both tracers, with heart/blood ratios observed to be below 0.5 at all time points, diminishing the potential of the synthesized complexes for cardiac imaging. Copyright © 2014 John Wiley & Sons, Ltd.